Discussions on water governance in the Paraguay (South America) and Tagus (Luso-Hispanic) river basins - Barbosa, Flávia Darre [UNESP] (Taylor & Francis, 2023)
This chapter provides a discussion on water governance within the scope of two international drainage basins, the Paraguay Basin in South America – with an emphasis on the relations between Brazil and Paraguay – and the Luso-Hispanic Tagus Basin, both of which experience situations of conflict to varying degrees. On the one hand, similar gaps were found, particularly regarding the inequity between governments, civil society, and the private sector in making decisions regarding the best way to manage water resources in a manner compatible with sustainable development and water security in the basins. On the other hand, it was possible to note the contribution of several norms and attitudes of certain stakeholders in different scales of participation, which contribute to water cooperation in the basins.